Politik Hukum Dalam Perda Berbasis Syari’ah - Moh. Mahfud MD. (Fakultas Hukum Universitas Islam Indonesia, 2007)
In the early of District Regulation Draft Reform merely determines four absolute matters which become the Central Government concerns namely foreign relation, moneter and national fiscal, national and security defend and judicature. However. before the Draft has been ratified by the Parliament, Indonesian Moslem Scholar Assembly with Department of Religion propose religious matter becomes the matter of the central goverment. Because , if it is decentralized will create a worry that will raise district regulation based on the majority religion of each district.